Daya Saing Destinasi MICE di Indonesia - Heri Setyawan (Sekolah Vokasi, Universitas Gadjah Mada, 2018)
This article discusses the types of tours with visitors who have business needs (business visitor). Tour with visitor aimed at business (MICE / business visitor) different from facet needs, handling with tour with visitor aim of recreation (leisure visitor). In terms of foreign exchange earnings that affect the economic sector is the reason, because spending MICE / business visitor is greater than the visitors with recreation purposes. The analysis of the discussion refers to the ICCA (International Congress and Convention Association) ranking. The findings suggest that the competitiveness of Indonesian MICE destinations and MICE city in Indonesia is still weak compared to neighboring countries of Singapore, Thailand and Malaysia. In order to competitiveness of MICE destinations in Indonesia, there are four factors that must be considered in the criteria and indicators of a MICE destination. These factors are accessibility, attraction, amenitas as well as human resources and stakeholder support. So that a region / region / city does not easily declare itself as a MICE destination.